Development and application of one-step multiplex Real-Time PCR for detection of three main pathogens associated with bovine neonatal diarrhea - Wang, Chaonan; Wang, Fang; Chang, Jitao; Jiang, Zhigang; Han, Yuxin; Wang, Meixi; Jing, Bo; Zhao, Aiyun; Yin, Xin (Frontiers in Cellular and Infection Microbiology, 2024)
Neonatal calf diarrhea (NCD) is one of the most common diseases in calves, causing huge economic and productivity losses to the bovine industry worldwide. The main pathogens include bovine rotavirus (BRV), bovine coronavirus (BCoV), and Enterotoxigenic Escherichia coli (ETEC) K99. Since multiple infectious agents can be involved in calf diarrhea, detecting each causative agent by traditional methods is laborious and expensive. Thus, this study developed a one-step multiplex Real-Time PCR assay to simultaneously detect BRV, BCoV, and E. coli K99 + . The established assay could specifically detect the target pathogens without cross-reactivity with other pathogens. A single real-time PCR can detect 1 copy/µL for each pathogen, and multiplex real-time PCR has a detection limit of 10 copies/µL. Reproducibility as measured by standard deviation and coefficient of variation were desirable. The assay performance on field samples was evaluated on 1100 rectal swabs of diseased cattle with diarrhea symptoms and compared with the conventional gel-based RT-PCR assay. Both methods are reasonably consistent, while the real-time PCR assay was more sensitive and could rapidly distinguish these three pathogens in one tube. The results suggested that the established assay has excellent specificity and sensitivity and was suitable for clinical application. Analysis of surveillance data showed that BRV and BCoV are major enteric viral pathogens accounting for calves' diarrhea in China. Overall, the robustness and high-throughput performance of the developed assay make it a powerful tool in diagnostic applications and calf diarrhea research. K99 (ETEC) are the most frequently identified causative factors(3-6). These pathogens are often mixed and lead to several complications. Thus, early diagnosis and treatment facilitate timely management and control of NCD.